HIV HGM biobank as a research platform for paediatric infectious diseases and COVID-19 pandemic - Consuegra, Irene; Jiménez, José Luis; Mellado, María José; Muñoz Fernández, María Ángeles (My University, 2022)
Aim: The initial cases of COVID-19 appeared in December 2019 and Spain was one of the most afected countries during the frst wave (March to June). Since then, HIV HGM BioBank has been restructured as an established Paediat¿ rics and Adults HIV_COVID-19 BioBank that aims at the long-term storage of samples obtained from not only HIV-1, but also from COVID-19 patients and HIV-1_COVID-19 coinfected patients. Methods: HIV HGM BioBank holds high quality biological samples from newborns, children, adolescents and adults with their associated clinical data. Research groups trying to establish large networks focused on research on specifc clinical problems in epidemiology, biology, routes of transmission and therapies, are potential users of the clinical samples and of associated data of HIV-1_COVID-19 HGM BioBank. Results: The HIV HGM BioBank is an academic and ethical enterprise complying with all the legal regulatory rules to provide service to the society. HIV_COVID-19 HGM BioBank has been repurposed to ofer an important resource for global research of COVID-19 in newborns, children, adolescents, adults and elders to study the biological efect of the pandemic. Conclusion: Herein, we present a description of how HIV HGM BioBank has rapidly become an indispensable struc¿ ture in modern biomedical research, including COVID-19 research